Failed plots: Authority and the social circle in eighteenth-century fiction. - Schellenberg, Elizabeth A. (University of Ottawa (Canada), 1991)
Theoreticians of the early novel have canonized as realistic those fictions that portray the desirous individual in sustained tension with his or her social environment. Such fictions bring irreconcilable and subversive voices into conflict, and privilege a strongly linear, teleological plot. This critical focus has contributed to the dismissal of a substantial body of eighteenth-century British fiction which adopts alternative structures in order to express different ideological alignments. In particular, a study of pairs of works by authors who may in the first case be relative unknowns, but in the second have become more established and authoritative writers seeking to meet audience expectations while balancing or competing an oeuvre, reveals divergent responses to a climate of philosophical uncertainty, social flux, and changing notions of authorship. The later work of each pair--Samuel Richardson's sequel to Pamela, his Sir Charles Grandison following upon Clarissa, Henry Fielding's Amelia after Tom Jones, and Sarah Fielding's sequel, Volume the Last, to her Adventures of David Simple--reflects its context of successful author, established audience, and preceding text by reinscribing the isolated protagonist within a stable social circle modelled on the intimate conversational group. Thus these works share a use of the circle as formal image at several levels of structure, ranging from metaphors of clockworks and gravitational systems, to "conversation-pieces" as the fundamental units of plot, to an overall impulse towards consensus and cyclical stasis that replaces the momentum supplied by conflict in their predecessor texts. Two examples taken from pre-novelistic genres--William Congreve's The Double-Dealer as a comedy self-consciously in search of a new form that will adequately embody the emerging ideal of conversational relations, and John Bunyan's sequel to The Pilgrim's Progress as a feminized, communal, and static rewriting of the individual's struggle to win salvation in a hostile world--suggest the preoccupations informing the conservative fictions studied in the thesis. (Abstract shortened by UMI.)
Keywords: Literature, English.